Production of Decolorized Mushroom Pulp for Nonwoven Cotton Composite - Ho-Seong Im; Satomi Tagawa; Jae-Seok Jeong; Hyun-Jae Shin (Fibers)
Cotton, widely used in the textile industry, has a significant environmental impact due to soil degradation and excessive water consumption during cultivation. As a result, there is a growing need for biodegradable alternatives. This study pioneers the development of decolorized mushroom pulps (DMPs) from edible mushrooms as a sustainable replacement for cotton. Decolorization of fruiting bodies showed the highest reactivity with hydrogen peroxide (H2O2). At the same time, mycelium responded more effectively to sodium hypochlorite (NaClO), though this led to structural changes such as melting and twisting. Potassium was detected in fruiting bodies but absent in mycelium, and higher salt content was noted in Agaricus bisporus and Trametes orientalis compared to Pleurotus ostreatus and Flammulina velutipes. Future research should focus on preserving mycelial integrity or developing strains that eliminate the need for decolorization treatments, advancing DMPs as viable biotextile materials.